2003
DOI: 10.1159/000072852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of spinocerebellar ataxia type 8 (SCA8)

Abstract: We previously reported that a transcribed but untranslated CTG expansion causes a novel form of ataxia, spinocerebellar ataxia type 8 (SCA8) (Koob et al., 1999). SCA8 was the first example of a dominant spinocerebellar ataxia that is not caused by the expansion of a CAG repeat translated into a polyglutamine tract. This slowly progressive form of ataxia is characterized by dramatic repeat instability and a high degree of reduced penetrance. The clinical and genetic features of the disease are discussed below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 56 publications
4
25
1
Order By: Relevance
“…The expansion, which contained 80 CTGNCAG repeats, preceded by 11 CTANTAG repeats, maps to chromosome 13q21. We subsequently found this expansion in a seven-generation ataxia kindred (the MN-A family), and by studying 92 members of that family were able to genetically confirm the relationship of the mutation to the clinical disease with a LOD score of 6.8 at h50.00 (2,4,5). According to our initial sequence analysis of the SCA8 CTGNCAG repeat region, there were no likely open reading frames identified in the CTG or CAG direction, but we initially showed that the CTG direction was transcribed, and that transcripts expressed and containing the CUG expansion are primarily expressed in the central nervous system and cerebellum (4).…”
Section: Identification Of the Sca8 Ctgncag Repeat Expansion Mutationmentioning
confidence: 98%
See 2 more Smart Citations
“…The expansion, which contained 80 CTGNCAG repeats, preceded by 11 CTANTAG repeats, maps to chromosome 13q21. We subsequently found this expansion in a seven-generation ataxia kindred (the MN-A family), and by studying 92 members of that family were able to genetically confirm the relationship of the mutation to the clinical disease with a LOD score of 6.8 at h50.00 (2,4,5). According to our initial sequence analysis of the SCA8 CTGNCAG repeat region, there were no likely open reading frames identified in the CTG or CAG direction, but we initially showed that the CTG direction was transcribed, and that transcripts expressed and containing the CUG expansion are primarily expressed in the central nervous system and cerebellum (4).…”
Section: Identification Of the Sca8 Ctgncag Repeat Expansion Mutationmentioning
confidence: 98%
“…This method, called repeat analysis, pooled isolation and detection (RAPID) cloning (2), used the repeat expansion detection (RED) assay (3), and several cloning and enrichment steps to identify CAGNCTG expansions and their corresponding flanking sequence (2,4,5). This method can be used to isolate candidate genes without requiring linkage studies and the identification of large families and provides a strategy for identifying genetic mutations causing diseases with reduced penetrance.…”
Section: Identification Of the Sca8 Ctgncag Repeat Expansion Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mismatches in triplet repeat structures have been hypothesized to be the origin of genetic instabilities that lead to DNA mutations [20][21][22][23][24][25]. During DNA replication, repair and recombination, slippage in single strands of CAG and CTG repeats can occur, forming slipped strand structures with AAEA and TAET mismatches, respectively [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Progression is slow, with ambulatory aids often not being required during the first 20 years of illness. Symptom severity correlates with repeat length and age (Mosemiller et al, 2003;Ikeda et al, 2004). One case with congenital onset presented with severe cerebellar symptoms in the first year, myoclonic epilepsy at 3 years, and mental retardation.…”
Section: Clinical Featuresmentioning
confidence: 99%